Fraud Auditing and Forensic Accounting. - Singleton, Tommie W. (Wiley corporate F & A series., 2010)
Praise for the Fourth Edition of Fraud Auditing and Forensic Accounting. "Tommie and Aaron Singleton have made important updates to a book I personally rely very heavily upon: Fraud Auditing and Forensic Accounting (FAFA). In the newest edition, they take difficult topics and explain them in straightforward actionable language. All my students benefitted from reading the third edition of the FAFA to better understand the issues and area of fraud and forensic accounting. With their singular focus on understandability and practicality, this Fourth Edition of the book makes a very important.